2015
DOI: 10.17017/jfish.v3i2.2015.111
|View full text |Cite
|
Sign up to set email alerts
|

Fishes of the river Padma, Bangladesh: Current trend and conservation status

Abstract: The Padma River is one of the longest rivers and it is believed to be an important spawning and feeding ground for riverine fish species of Bangladesh. This study was conducted from February 2013 to January 2014 and with a view to revealing the diversity of fish fauna in the river. A total of 71 species were recorded belonging to 10 orders, 26 families and 54 genera. The most dominant fish order was Cypriniformes contributing 28 species in 16 genera. Cyprinidae was most dominant family contributing 23 species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 5 publications
2
17
0
Order By: Relevance
“…The number of fish species recorded in the present study (67 species) was found higher than the fish species recorded in the Andharmanik River of Patuakhali district and Bookbhara Baor of Jessore district, where 53 and 38 fish species were found respectively (Mohsin et al 2009. Quite similar number of fish species was recorded from the Halti Beel (63) (Imteazzaman and Galib 2013), Atrai River (74) (Chaki et al 2014) and Padma River (Joadder et al 2015).…”
Section: Figuresupporting
confidence: 66%
See 2 more Smart Citations
“…The number of fish species recorded in the present study (67 species) was found higher than the fish species recorded in the Andharmanik River of Patuakhali district and Bookbhara Baor of Jessore district, where 53 and 38 fish species were found respectively (Mohsin et al 2009. Quite similar number of fish species was recorded from the Halti Beel (63) (Imteazzaman and Galib 2013), Atrai River (74) (Chaki et al 2014) and Padma River (Joadder et al 2015).…”
Section: Figuresupporting
confidence: 66%
“…In a more recent research, Hossain (2014) declared that a total of 30 riverine finfish species have been extinct from Bangladesh. Several research findings confirmed that loss of aquatic biodiversity, in terms of species composition and abundance, is very much conspicuous in the freshwater habitats of Bangladesh, primarily in rivers (Chaki et al 2014;Galib et al 2013;Joadder et al 2015;Mohsin et al 2013Mohsin et al , 2014.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Results obtained through studies undertaken by several researchers have revealed same scenario (Galib et al 2009aSamad et al 2010;Chaki et al 2014;Mohsin et al 2013Mohsin et al , 2014Galib 2015;Joadder et al 2015).…”
Section: Catch Analysismentioning
confidence: 68%
“…Critically Endangered, Endangered and Vulnerable. Decreasing trend of freshwater fishes in various rivers of Bangladesh has already been reported by several researchers (Galib 2015;Joadder et al 2015;Chaki et al 2014;Mohsin et al 2014Mohsin et al , 2013Galib et al 2013). In a recent research Hossain (2014a) declared that 30 riverine fish species have became extinct though the researcher did not mention the methodology followed for his findings.…”
Section: Introductionmentioning
confidence: 94%